Treatment of nightmares with prazosin: a systematic review (2012)
Nightmares, frequently associated with posttraumatic stress disorder and clinically relevant in today's world of violence, are difficult to treat, with few pharmacologic options. We performed a systematic review to evaluate the evidence for the use of prazosin in the treatment of nightmares. A comprehensive search was performed using the databases EMBASE, Ovid MEDLINE, PubMed, Scopus, Web of Science, and Cochrane Database of Systematic Reviews, from their inception to March 9, 2012, using keywords prazosin and nightmares/PTSD or associated terms (see text). Two authors independently reviewed titles and abstracts and selected relevant studies. Descriptive data and outcomes of interest from eligible studies were extracted by 1 author, and checked by 2 others. The risk of bias of randomized controlled trials (RCTs) was assessed independently by 2 reviewers. Articles met criteria for inclusion if prazosin was used to treat nightmares, and outcome measures included nightmares or related symptoms of sleep disorders. Our search yielded 21 studies, consisting of 4 RCTs, 4 open-label studies, 4 retrospective chart reviews, and 9 single case reports. The prazosin dose ranged from 1 to 16 mg/d. Results were mixed for the 4 RCTs: 3 reported significant improvement in the number of nightmares, and 1 found no reduction in the number of nightmares. Reduced nightmare severity with use of prazosin was consistently reported in the open-label trials, retrospective chart reviews, and single case reports.